Hydrophosphonylation of activated alkenes and alkynes via fluoride ion activation in ionic liquid medium - Balaraman, Ekambaram; Srinivas, Venu; Swamy, K. C. Kumara (Tetrahedron, 2009)
A simple transition metal-free hydro/hydrothiophosphonylation of Baylis–Hillman adducts, substituted allyl bromides, allenylphosphonates and alkynes, promoted by fluoride ion in ionic liquid, is described. Clear-cut evidence for fluoride activation of the phosphite via pentacoordinate phosphorus is provided for the first time. Also, in a comparative reaction, the product obtained was different from that from the palladium catalyzed one. Structures of key products are proven by X-ray crystallography.

Alkynyl and phosphonyl substituted nucleobases: a case of thermally induced conformational polymorphism - Swamy, K. C. Kumara; Allu, Srinivasarao; Srinivas, Venu; Balaraman, Ekambaram; Kumar, K. V. P. Pavan (Crystal Growth & Design, 2011)
Substituted nucleobases with alkynyl and phosphonyl groups were investigated in the context of supramolecular interactions and possible use toward synthesis of nucleoside phosphonic acids (NPAs). The adeninyl compound (adeninyl-N-9)-CH2CH2CH2CH2C≡CH exhibits conformational polymorphism as revealed by X-ray structures determined at 200 and 298 K. Interestingly, in the compound (adeninyl-N-9)-(CH2)15CH3, the long aliphatic carbon chain does not show disorder. A rather unusual bending of alkyl chain, likely due to C–H···O interactions, is observed in the case of the thymine compound (thyminyl)-CH2CH2CH2C≡CH that possesses a terminal alkyne group. The powerful hydrogen bond acceptor property of the phosphoryl oxygen (P═O) does not perturb (unless assisted by other hydrogen bonding partners) the homo base-pairing in the structures of most of the phosphonyl substituted nucleobases studied.

Cyclodiphosph(III)azane chemistry – ylides from the reaction of [(RNH)P-N(t-Bu)]2 [R = t-Bu, i-Pr] with dimethyl maleate and chiral ansa-type derivatives from reaction of [ClP-N(t-Bu)]2 with a substituted BINOL - Swamy, K.C. Kumara; Gangadhararao, G.; Srinivas, Venu; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Chakravarty, Manab (Inorganica Chimica Acta, 2011)
Use of a simple inorganic ring system with the cyclodiphosph(III)azane skeleton [e.g. [(RNH)P-N(t-Bu)]2 [R = t-Bu (7), i-Pr (8)] to probe some of the intermediates proposed in phosphine mediated organic reactions is highlighted. Thus the reaction of 7–8 with the allenylphosphine oxide Ph2P(O)C(Ph)double bond; length as m-dashCdouble bond; length as m-dashCH2 (9) affords the phosphinimines [(RNH)P(μ-N-t-Bu)2P(double bond; length as m-dashN-R)-C(double bond; length as m-dashCH2)CH(Ph)-P(O)Ph2] [R = t-Bu (10), i-Pr (11)], while a similar reaction of 7–8 with dimethyl maleate (or dimethyl fumarate) affords the ylides [(RNH)P(μ-N-t-Bu)2P(NH-R)double bond; length as m-dashC(CO2Me)-CH2(CO2Me) [R = t-Bu (18), i-Pr (19)]. The implication of such reactions on phosphine mediated organic transformations including Morita–Baylis–Hillman reaction is mentioned. In a rather rare type of situation, an unusually long phosphoryl (Pdouble bond; length as m-dashO) bond [1.538 (5) Å] as revealed the X-ray structure of {(R)-6,6′-(t-Bu)2-1,1′-(C10H5)2-2,2′-O2-}{P(O)(N-t-Bu)2-P(Se)} (27) is rationalized by means of crystallographic disorder in packing after comparing the data with that in the literature and {1,1′-(C10H6)2-2,2′-O2}{P(Se)(N-t-Bu)2-P(Se)} (29). X-ray structures of the new compounds 10–11, 18–19, 27 and 29 are discussed. Compound 10 crystallizes in the chiral space group Pca2(1) with (S)-chirality at the carbon center [–C(double bond; length as m-dashCH2)CH(Ph)-P] suggesting a case of spontaneous resolution through crystallization.